2016
DOI: 10.1007/s13555-016-0137-2
|View full text |Cite
|
Sign up to set email alerts
|

Ingenol Disoxate: A Novel 4-Isoxazolecarboxylate Ester of Ingenol with Improved Properties for Treatment of Actinic Keratosis and Other Non-Melanoma Skin Cancers

Abstract: IntroductionIngenol mebutate gel (Picato®, LEO Pharma A/S) is approved for the field treatment of actinic keratosis and is characterized by high sustained clearance of actinic lesions. The inherent propensity of ingenol mebutate towards chemical rearrangement necessitates refrigeration of the final product. We sought to identify novel ingenol derivatives with enhanced chemical stability and similar or improved in vitro potency and in vivo efficacy.MethodsA number of ingenol esters were synthesized with full re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Most of these proteins did not interact with ingenol (Figure C), which instead competitively blocked Ing-DAyne labeling of a mostly distinct subset of proteins in human cells (Figure S1D). We also performed an additional competition study in HSC-5 cells with a biologically active analogue of IngMebingenol disoxate ( 10 , IngDsx, Figure S2A)that shows enhanced chemical stability and is currently in phase 3 clinical development . We observed that the majority of high-occupancy protein targets for IngMeb were also targets of IngDsx (Figure S2B, Table S1), which tended to show higher competition ratios for these shared targets.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Most of these proteins did not interact with ingenol (Figure C), which instead competitively blocked Ing-DAyne labeling of a mostly distinct subset of proteins in human cells (Figure S1D). We also performed an additional competition study in HSC-5 cells with a biologically active analogue of IngMebingenol disoxate ( 10 , IngDsx, Figure S2A)that shows enhanced chemical stability and is currently in phase 3 clinical development . We observed that the majority of high-occupancy protein targets for IngMeb were also targets of IngDsx (Figure S2B, Table S1), which tended to show higher competition ratios for these shared targets.…”
Section: Resultsmentioning
confidence: 96%
“…Previous SAR studies demonstrated that ingenol itself is pharmacologically inactive 42 , 43 and the methylation of C5- or C20-hydroxyl groups of IngMeb also eliminates biological activity. 44 In addition, simultaneous removal of the C18/C19 methyl groups and dimethylcyclopropane moiety resulted in substantial loss in activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… (+)-Ingenol ( 11 ) was first isolated from Euphorbia ingens in 1968, and its derivatives have since been employed as effective treatments for the precancerous skin condition actinic keratosis. The potent analog, ingenol mebutate ( 46 ), marketed as Picato by LEO Pharma, is an FDA-approved topical treatment for the disease, whereas isoxazole derivative ingenol disoxate ( 47 ) is currently undergoing clinical trials for the same ailment . The preparation of these therapeutic agents presented a major obstacle for LEO Pharma, as only 275 mg of ingenol ( 11 ) can be isolated per kilogram of plant material .…”
Section: Total Synthesis Of Ingenolmentioning
confidence: 99%